Roles of irrigation schemes on household food security: the case of Mundi Mataga irrigation scheme. (Midlands State University, 2017)
The purpose of the study was to evaluate the role of Mundi-Mataga irrigation Scheme in improving household food security in Chikure Ward 26 in Mberengwa District. The study specifically sought to assess how the land was allocated to the beneficiaries in the scheme, examine the types of crops grown in the Mundi-Mataga irrigation Scheme, analyse the output trends in the Scheme and assess knowledge of farmers in the Mundi-Mataga irrigation Scheme. The study adopted a triangulation design which encompassed both qualitative and quantitative approaches. Random sampling was used to recruit primary participants in the study. Purposive sampling was used to recruit key informants into the study. The sample size for primary participants was 19. One person refused to participate in the study giving the study a non-response rate of 5%. Pretested, self-administered, semi-structured questionnaires were used to collect data from the primary participants (irrigators). An interviewer guide was used to collect data from key informants. The findings of the study are that farmers who were affected by the construction of the scheme were given first priority to choose the plots of their choices in the scheme. Males were the dominant plot holders who participated in the study constituting 58% (n=11). Female headed households had higher household composition (6-10). There was a decreasing trend in production, from 2008/9 season to 2012/13; of maize (from1.3 tons to 0.9 tons) and beans (from 0.9 tons in to 0.4 tons). There was an overall decrease in income generated from sale of produce from 2008/9 season to 2012/13 season. Maize decreased from $240 to $125, beans decreased from $560 to $80. There was no increase in income generated from sale of vegetables. There was an increase income generated of tomatoes from $45 to $55. In conclusion, the scheme is not realizing its full potential in addressing food security concerns in Mundi-Mataga Irrigation Scheme. Farmers are failing to meet expected outputs per hectare. The study, therefore recommends reintroduction of agricultural financing to boost productivity to fully address food security challenges in the area. The study further recommends periodic farmer education programs to adequately utilise the benefits of the irrigation scheme towards adequately addressing food challenges in the area.